A SEMANTIC ANALYSIS OF COGNITIVE MEANING IN BOB MARLEY’S SONG LYRICS - Tanjung, Dinda Andini; Asnani, Asnani (JOURNAL OF LANGUAGE, 2025)
This study explores the cognitive meanings in Bob Marley’s selected songs—One Love, Three Little Birds, and Could You Be Loved—through a semantic approach. Employing a qualitative descriptive method, it identifies meaning relations such as synonymy, antonymy, hyponymy, and polysemy within the lyrics. Findings reveal that Marley’s songs embody profound cognitive meanings, reflecting human experience, social values, and the struggle for justice. His poetic and symbolic language communicates universal messages of peace, solidarity, and resilience. The study demonstrates how cognitive semantics can illuminate the intersection of language, music, and social consciousness. Through a qualitative descriptive method and semantic analysis, the study identifies various meaning relations such as synonymy, antonymy, hyponymy, and polysemy that are embedded within the lyrics. Findings reveal that Marley’s songs embody profound cognitive meanings, reflecting human experience, social values, and the struggle for justice. His poetic and symbolic language communicates universal messages of peace, solidarity, and resilience. The study demonstrates how cognitive semantics can illuminate the intersection of language, music, and social consciousness.